Genetic Polymorphism in MMP9 May Be Associated With Anterior Open Bite in Children - Küchler,Erika Calvano (2017)
Abstract Anterior open bite (AOB) has a multifactorial etiology caused by the interaction of sucking habits and genetic factors. The aim of this study was to evaluate the association between AOB and polymorphisms in genes that encode Matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs). Four hundred and seventy-two children that presented at least one sucking habit were evaluated. Children were examined clinically for the presence of AOB. Genomic DNA was extracted from saliva. Genotyping of the selected polymorphisms in MMP2, MMP3, MMP9, TIMP1 and TIMP2 was carried out by real-time PCR using the TaqMan method. Allele and genotype frequencies were compared between the groups with and without AOB using the PLINK® software in a free and in a recessive model using a chi-square test. Logistic regression analysis was implemented (p≤0.05). Two hundred nineteen children had AOB while 253 did not. The polymorphism rs17576 in MMP9 was significantly associated with AOB (p=0.009). In a recessive model GG genotype was a protective factor for AOB (p=0.014; OR 4.6, 95%CI 1.3-16.2). In the logistic regression analysis, none of the genes was associated with AOB. In conclusion, the polymorphism rs17576 (glutamine for arginine substitution) in MMP9 was a protective factor for AOB.